Department location: Factor for Airbnb user’s valuation perception - Esparza Rodríguez, Saúl Alfonso; Martínez Arroyo, Jaime Apolinar; Ávila Carreón, Fernando (Mercados y Negocios, 2019)
The objective is to analyze the impact of the location in the quality perception of customers. Data was obtained from the stars-based valuation of Airbnb website, considering a standardized option of accommodation just apartments of one room up to two guest maximum, with an average cost of USD 50 per night and located in four cities: New York and Miami in USA, and Mexico City and Cancun in Mexico, using a chi-square analysis to identify if there is a difference in quality perception considering if the destination place have beach or not. The results showed than departments located in New York had the most significant difference in valuation of quality of hosts.